The aging effects of serial passaging in neural progenitor cells for in vitro neurodegenerative disease modelling - Low, Selwyn Jun Xi (2014)
Neural progenitor cells (NPCs) have been extensively used to model neurodegenerative diseases due to its ability to generate cell types of a neural lineage. As such diseases usually have a late onset, a defined in vitro model that mimics aging would be beneficial to aid the studying of the neurodegeneration process. In this study, the effects of serial passaging on the proliferation and differentiation capabilities of wild type (WT) and Parkinson's disease (PD) NPCs were evaluated by assessing gene expression changes across early and late passaged cells. Transcriptome analysis revealed roughly 1000 genes differentially expressed with increasing passage. Among which 18 genes were selected for validation. Both WT and PD cells showed a decrease in cell cycle markers with disease cells having an overall lower expression of cyclin D2 and higher levels of p21. Neurogenesis marker, NGN2 exhibited a significant decrease across passage along with a decline seen in various neuronal markers. These results indicate that serial passaging of NPCs could partially recapitulate the aging process in vitro, with disease cells showing a more evident reduction in cell cycle progression.